Contextualizing entrepreneurial identity among Syrian refugees in Jordan: The emergence of a destabilized habitus?. (November 2018) - Refai, Deema; Haloub, Radi; Lever, John
This article aims to contextualize the entrepreneurial identity (EI) of Syrian refugees living outside refugee camps in Jordan. The research adopts a social lens to consider the situation Syrians find themselves in by drawing on the work of Bourdieu. A qualitative design is applied to explore the different experiences and perceptions that pervade refugee stories and the work of refugee aid agencies. By contextualizing EI in the Jordanian context, the article reveals how a destabilized refugee habitus based on an embodied disposition of survivability is emerging. The article makes an empirical and conceptual contribution by highlighting how the entrepreneurial activities of Syrian refugees are driven by their experiences of the harsh social conditions they find themselves in.